Medial Patellofemoral Ligament Reconstruction Using Superficial Quadriceps Tendon Offers Satisfactory Results in Recurrent Patellar Dislocation - Sherchan, Binod; Humagain, Vaskar; Rai, Saroj (Nepal Orthopaedic Association Journal, 2020)
INTRODUCTION: This study aims to assess the functional outcomes of patients undergoing medial patellofemoral ligament reconstruction using superficial quadriceps tendon and also assess the postoperative complication and patient’s satisfaction level.METHODS: We retrospectively reviewed 33 patients (15 males, 18 females) with an average age of 19 years with recurrent patellar dislocation, operated from August 2015 to January 2018. Inclusion criteria of the study was patients with a recurrent patellar dislocation undergoing medial patellofemoral ligament reconstruction with a minimum follow-up of 1 year. Exclusion criteria of the study were: (1) associated ligamentous injuries of the knee joint, and (2) previous history of bony correction along with medial patellofemoral ligament reconstruction. The clinical evaluation was performed using Kujala knee score and visual analogue scale scores. Postoperative satisfaction level was performed using a self-constructed questionnaire.RESULTS: At the final follow-up, the mean Kujala score was significantly improved from 72 points (range 53-94) to 95 points (range 87-100) (p